The influence of GLP-1 on glucose-stimulated insulin secretion: Effects on β-cell sensitivity in type 2 and nondiabetic subjects - KJEMS, Lise L; HOLST, Jens J; VØLUND, Aage; MADSBAD, Sten (Diabetes (New York, N.Y.), 2003)
The intestinally derived hormone glucagon-like peptide 1 (GLP-1) (7-36 amide) has potent effects on glucose-mediated insulin secretion, insulin gene expression, and beta-cell growth and differentiation. It is, therefore, considered a potential therapeutic agent for the treatment of type 2 diabetes. However, the dose-response relationship between GLP-1 and basal and glucose-stimulated prehepatic insulin secretion rate (ISR) is currently not known. Seven patients with type 2 diabetes and seven matched nondiabetic control subjects were studied. ISR was determined during a graded glucose infusion of 2, 4, 6, 8, and 12 mg x kg(-1) x min(-1) over 150 min on four occasions with infusion of saline or GLP-1 at 0.5, 1.0, and 2.0 pmol x kg(-1) x min(-1). GLP-1 enhanced ISR in a dose-dependent manner during the graded glucose infusion from 332 +/- 51 to 975 +/- 198 pmol/kg in the patients with type 2 diabetes and from 711 +/- 123 to 2,415 +/- 243 pmol/kg in the control subjects. The beta-cell responsiveness to glucose, expressed as the slope of the linear relation between ISR and the glucose concentration, increased in proportion to the GLP-1 dose to 6 times relative to saline at the highest GLP-1 dose in the patients and 11 times in the control subjects, but it was 3 to 5 times lower in the patients with type 2 diabetes compared with healthy subjects at the same GLP-1 dose. During infusion of GLP-1 at 0.5 pmol x kg(-1) x min(-1) in the patients, the slope of ISR versus glucose became indistinguishable from that of the control subjects without GLP-1. Our results show that GLP-1 increases insulin secretion in patients with type 2 diabetes and control subjects in a dose-dependent manner and that the beta-cell responsiveness to glucose may be increased to normal levels with a low dose of GLP-1 infusion. Nevertheless, the results also indicate that the dose-response relation between beta-cell responsiveness to glucose and GLP-1 is severely impaired in patients with type 2 diabetes.